A nonlinear optimal control approach for the autonomous octorotor. Issue 3 (21st September 2020) - Rigatos, Gerasimos; Siano, Pierluigi; Abbaszadeh, Masoud; Monteriu, Andrea
Abstract : The article proposes a nonlinear optimal control approach for the model of the autonomous octorotor. This aerial drone has improved load transport capability due to being actuated by eight rotors. The dynamic model of the octorotor undergoes approximate linearization with the use of Taylor series expansion around a temporary operating point which is recomputed at each iteration of the control method. For the approximately linearized model an H‐infinity feedback controller is designed. The linearization procedure relies on the computation of the Jacobian matrices of the state‐space model of the octorotor. The proposed control method stands for the solution of the optimal control problem for the nonlinear and multivariable dynamics of this aerial drone, under model uncertainties, and external perturbations. For the computation of the controller's feedback gains an algebraic Riccati equation is solved at each time‐step of the control method. The new nonlinear optimal control approach achieves fast and accurate tracking for all state variables of the octorotor, under moderate variations of the control inputs. The stability properties of the control scheme are proven through Lyapunov analysis. It can be noted that: (1) the novelty/innovation of this research work is in presenting a novel and genuine nonlinear optimal control method for the octocopter's model, (2) the significance of the presented method is in achieving fast and accurate tracking of reference setpoints for the octocopter under moderate variations of the control inputs. By minimizing energy consumption by the actuators of the UAV its autonomy and operational capacity is improved, (3) the intellectual contribution of the article is in solving the nonlinear optimal control problem for the octocopter in an effective, yet computationally efficient manner. Abstract : A nonlinear optimal control method is developed for autonomous octorotors. The nonlinear model of the UAV undergoes linearization at each sampling instance around a time‐varying operating point. By solving an algebraic Riccati equation at each time‐step of the method a stabilizing H‐infinity feedback controller is designed. Global stability is proven through Lyapunov analysis